Arterial switch procedure and hybrid muscular ventricular septal defect closure in a patient with d-transposition of the great arteries and multiple ventricular septal defects: a case report and literature review. (14th December 2019) - Gibb, Jack J. C.; Caputo, Massimo; Taliotis, Demetris
Abstract: Hybrid cardiac surgery involves simultaneous catheter based and surgical treatment of heart diseases. We report a complete repair of dextro-transposition of the great arteries and perimembranous and muscular ventricular septal defects in a 5-month-old girl. This included an arterial switch operation followed by an off-bypass, echocardiographically guided per-ventricular muscular ventricular septal defect closure.